Cardiac surgeryEarly clinical outcomes of the surgical treatment of patients with aortic stenosis and small aortic annuli - Filip, Grzegorz; Bartuś, Krzysztof; Litwinowicz, Radosław; Konstanty-Kalandyk, Janusz; Bochenek, Maciej; Węgrzyn, Piotr; Kapelak, Bogusław; Wierzbicki, Karol; Bartuś, Magdalena; Sadowski, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: Aortic stenosis is the most common acquired valvular heart disease. In some patients with small aortic annuli, after the surgical implantation of the artificial aortic valve, patient-prosthesis mismatch (PPM) may be observed. It can lead to an increased transvalvular gradient and decreased reduction of left ventricular hypertrophy. PPM is detected in patients with iEOA < 0.85 cm2/m2. The aim of the study was the evaluation of PPM incidence in relation to the size of the prosthetic valves implanted in patients undergoing aortic valve replacement, as well as the perioperative assessment of treatment results of PPM patients. Material and methods: The study population included 92 patients, aged between 21 and 74 years old, who were implanted with St. Jude Medical mechanical aortic valves. The rate of complications and the echocardiographic parameters were evaluated. Patients were divided into three groups. The first study group consisted of 15 patients who underwent aortic valve implantation and received valves of small aortic annulus diameter (17 mm, 19 mm), the second group included 56 patients who received medium-sized valves (21 mm, 23 mm), and the third one consisted of 21 patients who were implanted with valves of large aortic annulus diameter (25 mm, 27 mm, 29 mm). Results: In the first group, PPM was diagnosed in all patients, in the second group in 92.9%, and in the third group in 52%. Perioperative mortality was 5.4%. Average transvalvular gradient in patients with small prostheses was 20.25 mm Hg, in patients with medium prostheses 13.42 mm Hg, and in patients with large prostheses 11 mm Hg.